Synthesis, Characterization and Antibacterial Activities of Manganese(II), Nickel(II), Copper(II) and Zinc(II) Complexes of the Hydrazone Compounds Derived from 1-Phenyl-3-methyl-4-acyl-pyrazole and Benzoyl Hydrazine - Zhu, Hualing; Zhu, Jinhua; Chen, Chen; Wei, Zhen; Tian, Lin (Asian Journal of Chemistry, 2013)
Manganese(II), nickel(II), copper(II) and zinc(II) complexes were prepared by the reactions of the correspondence metal acetate and the hydrazone ligands (L1-L3) derived from 1-phenyl-3-methyl-4-acyl-pyrazole and benzoyl hydrazine. The ligands (L1-L3) and metal complexes were characterized by elemental analysis and spectroscopic techniques such as 1H NMR and IR. Antimicrobial activity studies of (L1-L3) and the metal complexes against Escherichia coli and Bacillus subtilis were carried out by using disc diffusion method. The results indicate that the free ligands are more or less inactive against the two bacteria, the antibacterial abilities of the ligands become more pronounced when they are coordinated to the metal ions. The copper(II) complex of the benzoic acid [1-(5-methyl-3-oxo-2-phenyl-2,3-dihydro-1H-pyrazol-4-yl)ethylidene]hydrazide (L1) shows a significant inhibition to the growth of the two tested bacteria.